2021
DOI: 10.1111/jocn.15926
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and religiosity are associated with physical and psychological status in patients with chronic obstructive pulmonary disease

Abstract: Background: Management strategies that incorporate spirituality and religiosity (S/R) have been associated with better health status in clinical populations. However, few data are available for patients with chronic obstructive pulmonary disease (COPD) to improve the traditional disease-model treatment. Aims:The objectives of this study were to evaluate the association between S/R and physical and psychological status in patients with stable COPD.Design: This is a cross-sectional study.Methods: Religiosity, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 63 publications
1
33
0
Order By: Relevance
“…religiosity measured with a Duke Religion Index (DUREL) was not associated with QoL in this study (24). Similar results were reported by other authors (22), while according to others, faith subscale of FACIT-Sp score positively correlated with the scores of Multidimensional Index of Life Quality (MILQ) (18).…”
Section: Spiritual Well-being and Quality Of Life Of Copd Patientssupporting
confidence: 90%
See 1 more Smart Citation
“…religiosity measured with a Duke Religion Index (DUREL) was not associated with QoL in this study (24). Similar results were reported by other authors (22), while according to others, faith subscale of FACIT-Sp score positively correlated with the scores of Multidimensional Index of Life Quality (MILQ) (18).…”
Section: Spiritual Well-being and Quality Of Life Of Copd Patientssupporting
confidence: 90%
“…Spiritual well-being of individuals with COPD has been evaluated in a number of studies (17)(18)(19)(20)(21)(22)(23)(24) (Table 1). It was found to be similarly low among people with COPD and with inoperable lung cancer (18).…”
Section: Spiritual Well-being Of Individuals With Copdmentioning
confidence: 99%
“…The Function Assessment of Chronic Illness Therapy-Spiritual Scale (FACIT-SP-12) was used to assess the spirituality of COPD patients [ 27 , 28 , 47 ]. The scale contained 3 dimensions of peace, meaning, and faith, with 12 entries.…”
Section: Methodsmentioning
confidence: 99%
“…Helvaci et al [ 27 ] showed a significant positive correlation between spiritual health and medication adherence in COPD patients. Mendes et al [ 28 ] found that COPD patients with high levels of spiritual health showed less anxiety and depression, as well as better emotional functioning and disease control, suggesting better emotional management. Both medication management and emotional management are part of COPD self-management [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, as mentioned above, R/S has been studied in relation to physical health and has generally focused on the health of people with some type of physical pathology, such as respiratory disease [ 27 ], cardiovascular disease [ 28 ], or various types of chronic diseases [ 9 , 29 ]. Be that as it may, the relationships between R/S and physical health have been extensively documented [ 1 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%